Development of the learning application “pro kata kerja” based on the waterfall modelpembangunan aplikasi pembelajaran “pro kata kerja” berlandaskan model air terjun - Subramaniam, Vijayaletchumy; Vasuthevan, Pavitra; Janan, Dahlia (Universiti Putra Malaysia, 2026)
The mastery of derived verbs among pupils in Tamil vernacular schools remains at an alarming level, particularly in relation to the verb prefix meN- and its allomorphs. Pupils often commit errors in forming derived verbs due to the influence of their mother tongue, the lack of digital teaching aids, and the predominance of conventional teaching methods. Hence, this study was conducted to identify the needs and subsequently develop a learning application, “Pro Kata Kerja” based on interactive learning. The study employed both quantitative and qualitative research designs through written tests, questionnaires with Malay language teachers, and participatory observation. A total of 100 Year 5 pupils from Ladang Kinrara Tamil Vernacular School were selected as the research sample. This study is underpinned by Corder’s (1973) Error Analysis Theory, which explains that language errors are important indicators in understanding second language learning processes. The development of the learning application followed the Waterfall Model (Royce, 1970) and was supported by the Cognitive Information Processing Theory (Atkinson & Shiffrin, 1968). Findings revealed an urgent need for more interactive, contextual, and generation-appropriate learning aids for Generation Alpha. The application was developed with gamification features, exercises based on verb affixes, immediate feedback, and a user-friendly interface. The study’s findings prove that digital approaches can enhance grammar mastery in a more systematic and engaging manner.